Short‐term Effectiveness of a Modified Osteotomy for Total Elbow Joint Replacement in Patients of Hemophilic Elbow Arthritis with Severe Flexion Contracture Deformity: A Three‐Cases Series Report. Issue 10 (26th August 2022) - Cai, Gaorui; Song, Lixia; Chen, Guoneng; Yuan, Shanyou; Cai, Lisheng; Ning, Xianjia; Wang, Jinghua; Jiang, Wenxue
Abstract : Objective: To report the modified osteotomy and the short‐term effectiveness of the total elbow joint replacement in patients of hemophilic elbow arthritis with severe flexion contracture deformity. Methods: This study introduced the therapeutic approach of the total elbow joint replacement in patients of hemophilic elbow arthritis with severe flexion contracture deformity, and assessed the short‐term effectiveness in three cases (three elbows) of end‐stage hemophilic elbow arthritis admitted from October 2020 to December 2020. The included patients were all diagnosed with hemophilia A (factor VII deficiency), accompanied by severe bilateral elbow joint flexion contracture, which seriously affects daily life and requires surgical intervention. Clinical data and follow‐up results were analyzed before total elbow arthroplasty and 1, 3, and 6 months postoperatively. Pre‐ and postoperative range of motion, pain score, and function score were compared, and intraoperative and postoperative complications are reported. Results: All three patients were male, with an average age of 31 years. The main clinical manifestations were bilateral elbow arthritis with flexion contracture. Two of the patients underwent right elbow replacement, and one patient underwent left elbow replacement. All cases were followed up for 6 months postoperatively. No incision infection or ulnar nerve injury occurred. Postoperative triceps brachii muscle strength was slightly weakened compared with preoperative muscle strength. Average elbow flexion and extension range of motion was 60° (30°–100°) preoperatively and increased to 127° (110°–140°) postoperatively; rotational range of motion of the affected forearm was 47° (10°–85°) preoperatively and increased to 117° postoperatively. The mean visual analogue scale (VAS) was 6 (5–8) preoperatively and decreased to 3 (2–4) postoperatively. The mean MEPS score was 62 (55–75) and increased to 87 (80–95) postoperatively. During the follow‐up, anteroposterior and lateral radiographs showed no signs of prosthesis loosening in the elbow. Conclusions: For severe hemophilic elbow arthritis patients, the short‐term treatment effect of total elbow replacement is good, following the strict adherence to the surgical indications and proper preparation for the perioperative period. The modified osteotomy can fully expose the visual field and reduce complications of ulnar nerve injury. The long‐term effects need to be study future. Abstract : This paper reports an analysis of three cases (three elbows) of end‐stage hemophilic elbow arthritis that underwent total elbow arthroplasty. Results regarding perioperative complications and improvements in range of motion are among the most promising of case series published thus far.